Enhanced Lipid Profile in Plasma and Erythrocytes of Hypertensive Type-2-Diabetes Mellitus Subjects in South-Western Nigeria (Bangladesh Journal of Medical Biochemistry, 2018)
The growing burden of hypertension and type 2 diabetes mellitus (T2DM) in Nigeria and related cardiovascular complications is becoming a public health concern. Cardiovascular risk factors were evaluated in control subjects (n=150) and patients (n=470) [hypertensive nondiabetics (n=179), normotensive diabetics (n=132), hypertensive diabetics (n=159)] attending at the Medical Out-Patient Clinic of the State Hospital, Abeokuta, Nigeria. Cholesterol, triacylglycerols and phospholipids were determined spectrophotometrically in plasma, erythrocytes and lipoproteins. The presence of either or both diseases resulted in significant (p